PERAN PEREMPUAN DALAM RUMAH TANGGA PERSPEKTIF ISLAM: Kajian Tematik Dalam Alquran Dan Hadis - Eko Zulfikar (UIN Siber Syekh Nurjati Cirebon, 2019)
Parents are a family component consisting of father (husband) and mother (wife). They are the result of a sacred bond commonly called marriage. Each of them has an important role, especially in the mother (wife) because it is generally the most authoritative mother in forming a good household (sakinah). This paper will introduce how the role of women in the household perspective of the Islam. By using a thematic approach, this paper focused on the role of women as a wife and as a mother in the eyes of Alquran and hadith. Thus, it was found that the role of women as wives is at least three points; become husband’s partner biologically and psychologically, and become manager in managing the household. While the role of women as a mother at least there are three points as well; containing children, childbirth and breastfeeding, and nurturing and educating children.